2022
DOI: 10.14309/01.ajg.0000857284.41684.71
|View full text |Cite
|
Sign up to set email alerts
|

S161 Cold Snare Endoscopic Mucosal Resection for Colon Polyps: A Systematic Review and Meta-Analysis

Abstract: Introduction: Cold snare endoscopic mucosal resection (CS-EMR) has become increasingly popular for the removal of colon polyps . 10 mm. CS-EMR can potentially avert some of the risks associated with the use of electrocautery during polyp resection without compromising clinical efficacy. Therefore, we conducted a systematic review and meta-analysis to evaluate the efficacy and safety of CS-EMR in removing colon polyps. Methods: We conducted a comprehensive literature search of MEDLINE, EMBASE, Cochrane, Clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…However, alternative methods, such as logit or double arcsine transformation, could have been explored 2 . Reassuringly, the overall results seem to align with the conclusions of the individual studies included in our analysis 1 . As we clarified in the paper, we clearly stated that there were no reported perforations or post-polypectomy syndromes in the included studies.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…However, alternative methods, such as logit or double arcsine transformation, could have been explored 2 . Reassuringly, the overall results seem to align with the conclusions of the individual studies included in our analysis 1 . As we clarified in the paper, we clearly stated that there were no reported perforations or post-polypectomy syndromes in the included studies.…”
supporting
confidence: 81%
“…We appreciate the interest from Lv et al in our study “Cold snare endoscopic mucosal resection for colon polyps: a systematic review and meta-analysis” 1 . In this response, we seek to address their comments, clarify our methodological choices, and affirm the conclusions of our study.…”
mentioning
confidence: 97%
“…However, our modelled IRRs are consistent with recurrence rates reported in a recent systematic review. [21] Abdallah et al reported a recurrence rate of 12.3% (3.4%-35.7%) for polyps ≥20mm resected by piecemeal-cold snare polypectomy (P-CSP), derived from 4 studies. [13,[22][23][24] Unfortunately, recurrence rates for adenomas and sessile serrated lesions (SSLs) were not reported separately.…”
Section: Accepted Manuscriptmentioning
confidence: 99%